Drosophila melanogaster as a model for lead neurotoxicology and toxicogenomics research - Ruden, Douglas M.; Hirsch, Helmut V.; Lnenicka, Gregory; Possidente, Debra; Possidente, Bernard; Garfinkel, Mark D.; Wang, Luan (Frontiers in Genetics, 2012)
Drosophila melanogaster is an excellent model animal for studying the neurotoxicology of lead. It has been known since ancient Roman times that long-term exposure to low levels of lead results in behavioral abnormalities, such as what is now known as attention deficit hyperactivity disorder (ADHD). Because lead alters mechanisms that underlie developmental neuronal plasticity, chronic exposure of children, even at blood lead levels below the current CDC community action level (10 μg/dl), can result in reduced cognitive ability, increased likelihood of delinquency, behaviors associated with ADHD, changes in activity level, altered sensory function, delayed onset of sexual maturity in girls, and changes in immune function. In order to better understand how lead affects neuronal plasticity, we will describe recent findings from a Drosophila behavioral genetics laboratory, a Drosophila neurophysiology laboratory, and a Drosophila quantitative genetics laboratory who have joined forces to study the effects of lead on the Drosophila nervous system. Studying the effects of lead on Drosophila nervous system development will give us a better understanding of the mechanisms of Pb neurotoxicity in the developing human nervous system.